Financing national defense : policy and process - Jones, L. R.; Candreva, Philip J.; DeVore, Marc R. (Research in public management., 2012)
A myth from the colonial period was that Americans could defend themselves by keeping a rifle in the closet and when needed, grab it, and march off to battle in times of crisis. Unfortunately, providing national defense is more complicated that that; indeed it was more complicated even during the Revolutionary war. General George Washington's struggles to form a standing army supported by workable logistics and supply processes and to get funding for both from the Revolutionary Congress are well documented. Financing national defense requires planning and resourcing in advance. Reacting at the instant of crisis is too late. Building an educated, highly trained and capable Armed Forces and the acquisition of defense weapons and weapons systems has long lead times and involves making decisions the consequences of which are likely to last for decades. These decisions include how to recruit and retain military and civilian personnel as well as designing, buying and fielding a vast array of ground weapons, ships, aircraft and other weaponry. A decision to buy a major defense weapons system for example sets in motion a chain of other decisions that will affect the U.S., its allies and enemies around the world. Implementation of such decisions is financed through the U.S. federal government and Department of Defense budget processes in a planned yet highly and pluralistic and disaggregated system for determining how to advocate, acquire and allocate scarce resources in a manner that culminates in congressional and presidential approval. In this book we examine the concepts and practices of defense financing, provide a detailed description and analysis of resource policy decision making, financial management and budget execution processes, and analyze the most significant features of the national defense and U.S. federal government resource decision and management system. The book assesses the numerous factors, including those that characterize the complex budget review and appropriation decision making dynamics of Congress, that make U.S. defense finance and budgeting different from any other system in the world. In addition, in a concluding chapter the book compares U.S. defense policy and budgeting to other nations in different regions of the globe, drawing conclusions about the effects of U.S. defense policy and defense financing abroad in regions including Europe, Russia, the Middle-East and Asia.